PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD 3 PEGANJARAN - Ertanti, Pipit; Ratnasari, Yuni; Suhartati, Oktri; Fadhlil Wafi, Taris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was based on the issue of low student learning outcomes in Mathematics. The aim of this study was to determine the effect of the Student Team Achievement Division (STAD) cooperative learning model on the improvement of mathematics learning outcomes for third-grade students at SD 3 Peganjaran. The classroom action research was conducted in the third-grade class at SD 3 Peganjaran, with 12 students as the research subjects. The study was conducted over two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research instrument used was a test. The data analysis technique employed was quantitative. The results of the study show that the application of the Student Team Achievement Division (STAD) cooperative learning model can improve the mathematics learning outcomes of third-grade students at SD 3 Peganjaran. Students' learning outcomes improve from cycle I to cycle II, with the percentage of students achieving mastery increasing from 41.67% to 75%, and the average score rising from 63.75 to 76.67.